Angie's gladiator eaudiobook - Dixon, Ruby (Icehome, 2019)
As an a'ani warrior, my life matters little. Cloned from the same matter as thousands of others, I am but one of many. Here on the ice planet, though, I can start over. I can become my own person, have my own needs, my own wants. I know what I want. I have known since the moment I arrived. Her name is Angie. She is human, with sad, lonely eyes, and a very pregnant belly. To her, I am not just another clone. I am Vordis, the one who laughs at her jokes, tends to her needs, and makes her smile. I will do anything to make her mine. But my brother and fellow clone Thrand thinks the same way, and he's just as determined to win her. Will I have to destroy my bond with my brother to win my female? Or will he cause a rift between us that's impossible to mend? Contains mature themes.